The Effect of LPS and Ketoprofen on Cytokines, Brain Monoamines, and Social Behavior in Group-Housed Pigs - Veit, Christina; Janczak, Andrew M.; Ranheim, Birgit; Vas, Judit; Valros, Anna; Sandercock, Dale A.; Piepponen, Petteri; Dulgheriu, Daniela; Nordgreen, Janicke (Frontiers in Veterinary Science, 2021)
Poor health is a risk factor for damaging behaviors but the mechanisms behind this link are unknown. Injection of pigs with lipopolysaccharide (LPS) can be used to model aspects of poor health. Recent studies have shown LPS-injected pigs perform more tail- and ear- directed behavior compared to saline-injected pigs and suggest pro-inflammatory cytokines may play a role in these behaviors. The aim of this study was to test the effect of LPS on social behavior of pigs and neurotransmitters and -modulators in their brains, and to test the effect of a nonsteroidal anti-inflammatory drug (NSAID) on the effects of LPS. Fifty-two female pigs (11-12 weeks) were allocated to four treatments, comprising two injections: saline-saline (SS), saline-LPS (SL), ketoprofen-saline (KS), and ketoprofen-LPS (KL). Activity was scan sampled every 5 min for 6 h after the last injection in the pen. Social behavior was observed continuously in 10 x 15 min bouts between 8 am and 5 pm one day before (baseline) and one and two days after injection. Saliva was analyzed for cortisol and plasma for tryptophan and kynurenine. Frontal cortex, hippocampus, hypothalamus and brain stem were sampled 72 h after injection and analyzed for cytokines and monoamines. LPS activated the HPA-axis and decreased activity within 6 h after injection. Ketoprofen lowered the effect of LPS on cortisol release and attenuated behavioral signs of sickness in challenged pigs. SL pigs manipulated the ears of their pen mates significantly longer than SS pigs two days after injection. LPS had no observed effect on IFN-γ, TNF-α and IL-18. At 72 h after injection, plasma tryptophan was depleted in SL pigs and tryptophan and kynurenine concentrations in frontal cortex and brain stem of SL pigs were significantly lower compared to SS pigs. Dopamine concentrations in the hypothalamus of SL pigs were significantly lower compared to SS pigs. Serotonin concentrations in the hypothalamus and noradrenaline concentrations in the hippocampus of SL pigs were significantly lower compared to KL pigs. In conclusion, LPS influenced different neurotransmitters and -modulators in the brain that are hypothesized to play an important role in the regulation of mood and behavior.